Financial reporting, financial statement analysis, and valuation :A strategic perspective /James M. Wahlen, Stephen P. Baginski, Mark T. Bradshaw. - Wahlen, James M.
Helps students learn financial statement analysis effectively by performing the analysis on actual companies. This title also helps students learn to integrate the concepts from economics, business strategy, accounting, and other business disciplines through the integration of a six-step process.